The BIM towards the Cadastre of the Future enhanced through the Use of Technology (diségno, 2018)
Knowing, digitalizing, sharing represent the key concepts of this millennium. The construction and Real Estate sectors have theopportunity to take up this challenge by becoming promoters of intelligent data management that characterize buildings. The BuildingInformation Modelling (BIM) methodology, strengthened by the unstoppable technological progress, lays the groundwork forre-designing a structured knowledge system of the building heritage. This triggers a new concept of Cadastre of the Future, dynamicand updated, which interrogates the Big Data of the buildings according to a multidisciplinary and interoperable approach. Theperspective is ambitious, but it is essential to define the correct methodological approach to govern the digitization of built heritage.The setting up of the first experimentations is carried out on the City of Turin. Pursuing the vision of augmented digital city, aninteractive map has been created, exploiting new technologies, such as Augmented and Virtual Reality, to enable the disseminationof information to different types of users.
Keywords: Building Information Modelling; Cadastre of the Future; Big Data; Augmented Reality; Virtual Reality